Effects of Feed Supplement on Intestinal Histochemistry and Histoenzymology on Broiler Chickens (Gallus domesticus) - Saini, Jyoti (Indian Journal of Veterinary Anatomy, 2020)
A feeding trial on 210 day old chicks was conducted to investigate the effects of feed supplementations on broiler intestinal histochemistry and histoenzymology. To conduct this investigation Experimental treatments were: 1) control, 2) control + cocktail enzymes, 3) control + prebiotic, 4) control + probiotic, 5) control + organic acid 6) control + antioxidant and 7) control + saponin and inulin. Birds were collected, euthanized, dissected and then specimens were processed for histochemistry and histoenzymology staining techniques. Histochemical findings Histoenzymic study revealed the PAS reaction in the lamina propria, glands of Lieberkuhn and goblet cells from day 1 to 35 in all treatments. Strong epithelial mucin was demonstrated in the intestinal goblet cells of middle segments of the small intestine in the birds of all the treatments. Alcian-Blue stain revealed the strong reaction of acid mucin in the villi as well as gland epithelium of the ileum of 14 day old birds. PAS and PAS/ AB activity was variable in different segments of intestine.